Strengthening management of non-communicable diseases in primary care, Malawi: A short report - Amos Mailosi; Christina Miller; Catherine Hodge; Serah Msimuko (AOSIS, 2021)
Within the community-orientated primary care module for training family physicians at the Kamuzu University of Health Sciences in Malawi, a relationship was formed between Nkhoma Mission Hospital's Family Medicine Department and the Diamphwe Community Health Centre (HC) to strengthen the continuity of healthcare and capacity team building. The initial focus was on improving the management of hypertension and diabetes in terms of diagnosis, tracking of the patients in a registry and timely referral to secondary care facilities The relationship has received positive support from Diamphwe healthcare workers, which then improved the management of non-communicable diseases and patient care at Diamphwe. It has also shown how family medicine physicians can improve HC capacity through support and mentorship.